Implementation of Group Counseling Services Based on Cognitive Behavior Modification with Self-Management Techniques to Reduce Nomophobia among Senior High School Students - Nasution, Ahmad Zaki Ilman; Karneli, Yeni; Hariko, Rezki; Fikri, Miftahul (Journal of Educational, Health and Community Psychology, 2025)
Nomophobia, defined as excessive anxiety due to the absence of access to smartphones, has become a widespread psychological problem that disrupts students' concentration, motivation, and academic achievement. As many as 84.2% of high school students in Indonesia have been reported to experience severe nomophobia symptoms. This quasi-experimental study aims to test the effectiveness of group counseling services based on the Cognitive Behavior Modification (CBM) approach integrated with self-management techniques in reducing nomophobic behavior among high school students. A total of 20 eleventh grade students (aged 16–17 years) at SMA Negeri 17 Padang were divided into two groups: an experimental group (n = 10) that received five sessions of group counseling based on Cognitive Behavior Modification (CBM) with self-management techniques, and a control group (n = 10) that received conventional counseling. Data were collected using an adapted version of the Nomophobia Questionnaire (NMP-Q) (33 items, four dimensions, α = 0.781) and analyzed with nonparametric tests (Wilcoxon Signed-Rank Test and Mann-Whitney U Test) at a significance level of α = 0.05. The research results showed that the experimental group experienced a significant decrease of 41.3% (from M = 121.7, high category, to M = 84.7, low category), compared to the control group which only decreased by 12.9% (from M = 116.4 to M = 105.8). Statistical analysis showed significant differences both within groups (Wilcoxon Z = -2.803, p = 0.005) and between groups (Mann-Whitney U = 11.500, Z = -2.911, p = 0.004). Group counseling based on Cognitive Behavior Modification (CBM) integrated with self-management techniques proved effective in reducing nomophobic behavior through cognitive restructuring and self-regulation, and is therefore recommended as a structured intervention to address technology related anxiety in educational settings.